Occupational Health Safety of Health Professionals and Associated Factors During COVID-19 Pandemics at North Showa Zone, Oromia Regional State, Ethiopia - Hailu D; Benayew M; Liknaw T; Ayenew M; Ayalew AF; Ayano B; Adera A; Tesema M; Gezahegn A; Birhanu T; Wendimu E (Dove Medical Press, 2021)
Dejene Hailu,1 Mengistu Benayew,1 Tiliksew Liknaw,1 Muluken Ayenew,1 Agumas Fentahun Ayalew,2 Bizuneh Ayano,2 Addis Adera,2 Mengistu Tesema,2 Andualem Gezahegn,3 Tadesse Birhanu,4 Eshetu Wendimu5 1Department of Nursing, College of Health Sciences, Salale University, Fitche, Ethiopia; 2Department of Public Health, College of Health Sciences, Salale University, Fitche, Ethiopia; 3Department of Midwifery, College of Health Science, Salale University, Fitche, Ethiopia; 4Tropical and Infectious Disease, Salale University, Fitche, Ethiopia; 5Research and Community Services Vice President, Salale University, Fitche, EthiopiaCorrespondence: Dejene Hailu Email dejenehailu77@yahoo.comBackground: Coronavirus disease 19 was observed as a pandemic and caused many community health problems that resulted in Global issues. It causes death for many individuals including health professionals. This study aimed to determine the occupational health safety of health professionals and associated factors during COVID-19 pandemic at North Showa.Methods: Institutions-based Cross-sectional study was conducted using a simple random sampling technique from May 10 to June 15, 2020. Interviewer-administered questioners were used, and data were entered into Epi-data version 3.1 and exported to SPSS 23 for analysis. Bi-variable logistic regression was carried out to select candidate variables with a cutoff point < 0.2. Finally, multivariable logistic regression was conducted to identify significant variables. An adjusted odds ratio with 95% CI at a 5% level of significance was used to measure the strength of association. P-value < 0.05 indicated a significant association between variables.Results: A total of 280 health professionals participated with a 92.72% response rate. Of which 57.9% (n=162) were males while 42.1% (n=118) females. Of total 48.9% (n=137) (95% CI: 43.2, 55.0) health professionals had poor occupational health and safety. Availability of soap and bleach (AOR=2.50; 1.439, 4.356), Possibility of isolate COVID-19 suspected clients (AOR=2.525; 1.690, 5.062), Availability of infections prevention and control program standards and policy (AOR=2.329; 1.325, 4.092), Availability of policy and procedure to prevent COVID-19 (AOR= 2.427; 1.389, 4.240) were significantly associated.Conclusion: The result suggested that occupational health safety was generally low in the study area. Therefore, a preventive measure such as the use of personal protective equipment and adherence to hand hygiene practice and Infection prevention policy could reduce the spread of COVID-19 and further study should be conducted to generate more evidence on determinants of occupational health safety.Keywords: occupational health, COVID-19, safety, Ethiopia